(untitled) (Heritage, 2020)
This study aims to show the historical and cultural context of English loanwords in Japanese, the process of domestication, and the functions performed by English loanwords. The orthographic, phonetic, morphological, semantic, and syntactic modifications of borrowed words have helped their assimilation. However, linguistic and cultural loanwords have, to a certain extent, remained separated from the Japanese language and culture, which resulted in the westernization of the Japanese life and language. As a result of the economic, political, and cultural influence of Great Britain and the United States and the imposition of English as the international language, a number of world languages have adopted foreign words from English, most notably in the 20th century. There are thousands of such loanwords in the Japanese language. Many of them are well-established in the language and in everyday use. The Japanese isolation from the West was interrupted by the arrival of the US war ships at the Tokyo port in the mid-19th century. The nation was urged to accept American requests to open trade routes and diplomacy, which had further affected linguistic changes and the enrichment of the Japanese language with numerous foreign words. In the 1930s, the Japanese government was against the introduction of foreign cultures; thus, leading to the elimination of foreign words from the language during the war. However, during the six-year US occupation, the Americans oversaw and greatly influenced the rebuilding of the Japanese society. Once again, Japan invested tremendous effort to westernize its society. The eliminated words again returned to the language, and the “boom” of foreign culture adoption was restored, which has remained the case until today. The study “nihon no sankoutosho", Reference books of Japan, published by Nihon toshoukan kyoukai (Japan Association of Libraries 1980) shows that, , aided by the spread of mass media, over a half of the 25,000 borrowed words in the Kadokawa’s Loanword Dictionary entered the Japanese language after World War II and most of them are taken from English. When the elements of one foreign culture and language are lent to another language, they adapt to its new cultural and linguistic context. The majority of loanwords in Japanese exhibit an orthographic, phonological, structural or semantic connection with the linguistic system of the language from which they are taken. The need to add vowels to English words to fit into the syllabic structure of the Japanese language resulted in very long loanwords. Borrowed words are often abbreviated either upon or after entering the language. This usually involves cutting off the end of a word that is left out. Blending has also occurred - it is obtained by a combination of abbreviated words which results in new expressions that do not exist in English.